Localización poco frecuente de Hidatidosis humana - Silva, Juan Jorge; Lanzaeta, G.; Rocha, L.; Silva, Cecilia (Revista Hospital Clínico Universidad de Chile, 1996)
UNUSUAL Sll’E OF HUMAN HYDATIDOSIS A case of a 63 years old woman with splenic hydatidosis without other complications is treated with splenectomy, previous esterilization of the cyst with saline solution ( 30%).